Visualizing Gene Expression Data via Voronoi Treemaps - Bernhardt, Jörg; Funke, Stefan; Hecker, Michael; Siebourg, Juliane (ISVD'09: Proceedings of the International Symposium on Voronoi Diagrams, 2009)
We investigate the use of Voronoi Treemaps to visualize complex biological data from gene expression analysis in conjunction with hierarchical classifications like Gene Ontology or KEGG Orthology.